Fatigue life prediction of 2524‐T3 and 7075‐T62 thin‐sheet aluminium alloy with an initial impact dent under block spectrum loading. Issue 4 (10th January 2021) - Chen, D.; Cheng, Z.Q.; Cunningham, P.R.; Xiong, J.J.
Abstract: This paper presents a fatigue life prediction model of post‐impacted sheets considering the effects of dent size and stress ratio. Low‐velocity impact tests at four different impact energies were performed on specimens cut from sheets of 2524‐T3 and 7075‐T62 aluminium alloy. Following the impact tests, static tensile and uni‐axial constant amplitude and block spectrum fatigue experiments were conducted. Numerical models were generated to determine the initial residual stress patterns, residual stress relaxation, and stress concentration factors around the impact dent. The S ‐ N curves and corresponding stress concentration factors and relaxed residual stresses of three of the post‐impacted specimens were used to determine the model parameters. Good agreement was achieved between the predictions and experimental results, and it has been demonstrated that the fatigue life prediction model can effectively simulate the effects of residual stress, stress concentration, and stress ratio on fatigue damage for post‐impacted thin sheet aluminium alloy materials.